Arc building through bimodal magmatism: The Tsukuba Igneous Complex, Japan, and its correlations and connections. Issue 16 (8th September 2022) - Wang, Jing-Yi; Santosh, M.; Tsunogae, Toshiaki; Kim, Sung Won; Dong, Yun-Peng
ABSTRACT: Subduction zones are the gateways of large-scale material and energy exchange. The SW Japan region is one of the important regions to understand ongoing convergent margin processes with continuous island arc magmatism. Here we investigate the bimodal magmatic suites from the Tsukuba area in Japan based on petrology, geochemistry and zircon U-Pb-Hf isotopes. Magmatic rocks in the Tsukuba area comprise two compositionally different groups: 1) a mafic group comprising Hbl-gabbros of ~66 Ma and 2) a felsic group represented by two pulses of granitoids at ~66 Ma and ~78 Ma, respectively. All these rocks display calc-alkaline affinity and negative Nb, and Ta anomalies, with a bimodal classification represented by a significant silica gap between the mafic and felsic members. The Hbl-gabbro witnessed plagioclase and amphibole fractionation as evidenced by the humped REE pattern and positive Eu and Sr anomalies. Zircon grains from the Hbl-gabbros show ƐHf (t) values in the range of −7.7 to −4.0 with a peak at −6.4, indicating an enriched mantle source modified by slab-derived fluids. The petrological and geochemical characteristics of Hbl-gabbros are similar to those in the magmatic suite of SW Japan, suggesting that Cretaceous arc magmatism in Tsukuba is an extension of the coeval magmatic belt in SW Japan. Two pulses of granitoids identified in this study are similar in composition and are both classified as I-type granite. The relative uniform high SiO2 (70–75%) and large variation of Hf isotope (−21.0 to −4.0) indicates the granitoids formed by lower crustal melting. The Hf model ages (2479–1392 Ma) of granitoids are significantly older than those of coeval granitoids in SW Japan which show Nd model ages at 1435–748 Ma. This indicates that the arc magmatism in the Tsukuba area involved older lower crust linked to a possible micro-continent derived from the Southern Korean Peninsula. Graphical abstract: uf0001